Principles of Language Politeness in Najwa's Eyes in Trans 7 - Mulia Agustina; Jamilin Tinambunan; Sri Rahayu (UIR Press, 2022)
This research is motivated by a violation of the principle of politeness in language, because the event is more dominant with questions. The problem studied in this study is how are the maxims of wisdom, generosity, appreciation, simplicity, consensus and sympathy in the principles of language politeness in the speech of the presenters and guest stars in the Mata Najwa program on Trans 7? This study aims to describe, analyze, and interpret